New approach of Municipal Solid Waste (MSW) leachate treatment using hydrothermal method - Khamis, Siti Salwa; Purwanto, Hadi; Mohd Salleh, Hamzah; Abd. Rahman, Mohamed; Rozhan, Alya Naili (The Mattingley Publishing Co., Inc., 2020)
Landfill is the most widely used and prevalent method for municipal solid waste disposal in Malaysia due to the cheap and simpler operational mechanism. However, leachate generation from MSW caused major pollution in the landfill due to it high toxicity. Current approach involving biological and physical/chemical leachate treatment are inadequate because of long processing time and/or relatively high-cost of processing. In this study, hydrothermal treatment at 150 °C under 0.15 MPa were investigated to treat MSW leachate. Laboratories studies were conducted to design the hydrothermal processing for leachate treatment and evaluate its process condition as well as to investigate the effect of parameters in the process for leachate treatment. Leachate characterization such as pH, chemical oxygen demand (COD), and ammonia nitrogen (NH3-N) was carried out before and after the treatment for comparison and recommendations. Result of characterization shows that in 2 hours of treatment, pH increased from 3.27 to 4.68, COD decreased from 51000 mg/L to 1100 mg/L and NH3-N decreased from 3496 mg/L to 152 mg/L. As such, hydrothermal treatment processing of MSW leachate is believed potentially as a leachate treatment process that is green and environmentally friendly technology that can shorter processing time and reduce operational cost.